Distúrbios do sono em adultos de uma cidade do Estado de São Paulo - Zanuto, Everton Alex Carvalho; Lima, Manoel Carlos Spiguel De; Araújo, Rafael Gavassa De; Silva, Eduardo Pereira Da; Anzolin, Caroline Cristina; Araujo, Monique Yndawe Castanho; Codogno, Jamile Sanches; Christofaro, Diego Giulliano Destro; Fernandes, Rômulo Araújo (Associação Brasileira de Saúde Coletiva, 2015)
OBJECTIVE:To analyze the occurrence of sleep-related disorders among adults from Presidente Prudente, Brazil, as well as to identify associations with behavioral, socio-demographic and nutritional status variables.METHODS:After random selection of the sample, interviews were performed with 743 adults of both genders, living in Presidente Prudente, Brazil. Sleep-related disorders, demographic variables (sex, age, ethnicity and schooling), behavioral variables (leisure physical activity, alcohol consumption, and smoking) and nutritional status were analyzed by questionnaires.RESULTS:The prevalence of sleep-related disorders was 46.7%, with 95% confidence interval (95%CI) 43.1 - 50.2. In the multivariate analysis, female sex, with odds ratio (OR) 1.74 (95%CI 1.26 - 2.40), schooling (OR = 0.49; 95%CI 0.28 - 0.82), overweight (OR = 1.99; 95%CI 1.39 - 2.85) and obesity (OR = 2.90; 95%CI 1.94 - 4.35) were associated with sleep-related disorders.CONCLUSION:There is high occurrence of sleep-related disorders in this sample, which was associated with female sex, lower schooling, overweight and obesity.

OBJETIVO:Analisar a ocorrência de distúrbios relacionados ao sono entre adultos de Presidente Prudente, São Paulo, bem como identificar suas associações com variáveis comportamentais, sociodemográficas e de estado nutricional.MÉTODOS:Após a seleção aleatória da amostra, foram realizadas entrevistas face a face com 743 adultos de ambos os sexos, residentes na cidade de Presidente Prudente, São Paulo. Foram aplicados questionários para análise de distúrbios relacionados ao sono, variáveis sociodemográficas (sexo, idade, etnia, escolaridade), comportamentais (atividade física no lazer, etilismo e tabagismo) e de estado nutricional.RESULTADOS:Foram observados distúrbios relacionados ao sono em 46,7% da amostra, com intervalo de confiança de 95% (IC95%) 43,1 - 50,2. Após a análise multivariada, foi observado que o sexo feminino, com odds ratio (OR) = 1,74 (IC95% 1,26 - 2,40), escolaridade (OR = 0,49; IC95% 0,28 - 0,82), sobrepeso (OR = 1,99; IC95% 1,39 - 2,85) e obesidade (OR = 2,90; IC95% 1,94 - 4,35) foram associados à ocorrência de distúrbios relacionados ao sono.CONCLUSÃO:É elevada a ocorrência de distúrbios de sono na amostra analisada, os quais foram mais frequentes em mulheres, pessoas de menor escolaridade e com sobrepeso e obesidade.
Sleep disturbances in adults in a city of Sao Paulo state
Keywords: Sleep initiation and maintenance disorders; Sleep; Motor activity; Overweight; Obesity; Educational status; Distúrbios do início e manutenção do sono; Sono; Atividade motora; Sobrepeso; Obesidade; Escolaridade